Effects of Kratom (Mitragyna speciosa) Hydrogel Application on Pancreatic Histopathology in Type 2 Diabetic Mice - Muhammad Aqil Siroj Jazuli; Zainul Hadi Wildan Ismail; Khuzaimah Nur Juhanifah Rihhadatulays; Eka Satria Akbar Ferdinan Hanafi; Puspita Rahmatul Jinan; Rosandhy Alifyah Pramesti; Hotimah Masdan Salim; Tri Wahyuni Bintarti (UNUSA Press, 2025)
Background: Type 2 diabetes mellitus is a metabolic disorder characterized by elevated blood glucose caused by insulin resistance and impaired insulin production by pancreatic β-cells due to oxidative stress. Kratom (Mitragyna speciosa) has been widely investigated for its antidiabetic, anti-inflammatory, and antioxidant effects, attributed to its alkaloid, flavonoid, phenolic, and saponin contents. This study aimed to evaluate the potential of topical kratom hydrogel as an innovative approach to improving pancreatic histology in type 2 diabetic mice, which has not been previously reported. Methods: Fifteen mice were divided into three groups: untreated diabetic group (DM), diabetic group treated with 5% kratom hydrogel (K5), and diabetic group treated with 15% kratom hydrogel (K15). Treatments were administered for two weeks. Parameters assessed included the percentage of healthy β-cells and acinar cells, as well as histological scoring of islet damage. Data were analyzed using parametric or non-parametric tests according to the normality distribution of each parameter. Results: Administration of 5% kratom hydrogel significantly increased the percentage of healthy β-cells (p<0.05) compared with 15% kratom hydrogel, which unexpectedly showed a lower proportion of healthy cells than the untreated group. Interestingly, the higher dose appeared to exert more toxic effects, whereas the lower dose provided better protective effects. No significant differences were observed in acinar cell parameters or islet damage scores, possibly due to the limited sample size. Conclusion: These findings provide preliminary evidence supporting the systemic therapeutic potential of topical kratom hydrogel, particularly in determining the effective dose and the need for larger sample sizes to obtain more consistent outcomes.